2014
DOI: 10.1371/journal.pgen.1004158
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Analysis Predicts an Epigenetic Switch for GATA Factor Expression in Endometriosis

Abstract: Endometriosis is a gynecological disease defined by the extrauterine growth of endometrial-like cells that cause chronic pain and infertility. The disease is limited to primates that exhibit spontaneous decidualization, and diseased cells are characterized by significant defects in the steroid-dependent genetic pathways that typify this process. Altered DNA methylation may underlie these defects, but few regions with differential methylation have been implicated in the disease. We mapped genome-wide difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
182
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(201 citation statements)
references
References 92 publications
8
182
0
11
Order By: Relevance
“…За последние годы в англоязычной литературе появились десятки публикаций, описывающих разницу в экспрессии факторов регуляции иммунного статуса [17], апоптотической активности [18], метастатического потенциала [19], наблюдае-мую между эктопическим и эутопическим эпи-телием. Ряд публикаций посвящен исследова-нию разницы эпигенетических особенностей: метилированию [20,21], экспрессии регуля-торных молекул РНк [22] и др. Результаты этих исследований носят описательный характер и плохо сопоставимы.…”
Section: наследуемые генетические признаки предрасположенности к эндоunclassified
See 1 more Smart Citation
“…За последние годы в англоязычной литературе появились десятки публикаций, описывающих разницу в экспрессии факторов регуляции иммунного статуса [17], апоптотической активности [18], метастатического потенциала [19], наблюдае-мую между эктопическим и эутопическим эпи-телием. Ряд публикаций посвящен исследова-нию разницы эпигенетических особенностей: метилированию [20,21], экспрессии регуля-торных молекул РНк [22] и др. Результаты этих исследований носят описательный характер и плохо сопоставимы.…”
Section: наследуемые генетические признаки предрасположенности к эндоunclassified
“…1. Supervised hierarchical clustering analysis of 72 differentially expressed genes between the 13 eutopic endometrium samples from eight endometriosis patients (EU 11,19,6,1,21,7,18,5) and five healthy control subjects (n 16,8,12,2,19). The expression levels are indicated using colors.…”
Section: экспрессионные особенности эутопического эндометия у пациентmentioning
confidence: 99%
“…Aberrant DNA methylation has been identified as a vital mechanism in tumorigenesis and multiple other diseases [8,9]. A recent study analyzed the genome-wide DNA methylation in patients with endometriosis and identified 42,248 differentially methylated CpGs in the endometriosis cells as compared to the healthy cells [10]. The homeobox gene (HOX) clusters were some of the maximum differentially methylated families of genes [10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study analyzed the genome-wide DNA methylation in patients with endometriosis and identified 42,248 differentially methylated CpGs in the endometriosis cells as compared to the healthy cells [10]. The homeobox gene (HOX) clusters were some of the maximum differentially methylated families of genes [10]. HOX genes are dynamically expressed in the endometrium, where they are necessary for endometrial growth, differentiation, and implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Full differentiation and maintenance of the decidua is contingent upon pregnancy, since the absence of a conceptus provokes shedding of the pre-decidualized endometrial layer and menstruation, and it has been suggested that the evolution of spontaneous decidualization necessitated menstruation (3). This intriguing observation led us to propose that the gene regulatory pathways that coordinate spontaneous decidualization in menstruating primates are the key pathways dysregulated in endometriosis (4). …”
Section: Introductionmentioning
confidence: 99%